The role of kinesiology in injury prevention in UNNES badminton ukm athletes - Wicaksono, Ryan Adi; Haryono, Sri; Pratama, Rivan Saghita (Jurnal Ilmu Keolahragaan, 2024)
This article describes the role of kinesiology in injury prevention in badminton players of the Student Activity Unit (UKM) of Semarang State University (UNNES). Kinesiology, the study of human movement, is important in the world of sports to prevent injuries that can affect an athlete's performance. This study used a qualitative method to understand how the application of kinematics principles can help reduce the risk of injury to badminton players. Data was collected through in-depth interviews with coaches, physical therapists, and athletes, as well as observations during training sessions. This study shows that kinesiology knowledge and its application to training programs plays an important role in increasing athletes' awareness of correct posture and technique, ultimately reducing the risk of injury. In addition, this study also identified the following challenges in the application of kinesiology: B. Lack of deep understanding between coaches and players and limited facilities. These results highlight the importance of continuing kinesiology education in athletic training programs at the university level and the need for institutional support to improve the quality of training. This article contributes to the literature on injury prevention in sports, particularly badminton in an academic setting.